РEЗУЛЬТAТИ EКCПEРИМEНТAЛЬНOГO ВПРOВAДЖEННЯ OCНOВНИX ПOЛOЖEНЬ ПCИXOЛOГO-ПEДAГOГIЧНOЇ КOНЦEПЦIЇ РOЗВИТКУ IНШOМOВНOЇ КOМУНIКAТИВНOЇ КОМПЕТЕНТНОСТІ - Oлeкcaндрeнкo Катерина (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розкрито структуру проблемно-комунікативного підходу і представлено аналіз результатів його впровадження в процесі викладання іноземної мови майбутніх фахівців з міжнародних відносин. Метою експериментального впровадження представленого вище підходу є розвиток іншомовної комунікативної компетентності студентів, від рівня сформованості якої залежить успіх їхньої професійної діяльності у майбутньому. Раскрыта структура проблемно-коммуникативного подхода и представлен анализ результатов его внедрения в процессе преподавания иностранного языка будущим специалистам по международным отношениям. Целью экспериментального внедрения представленного выше подхода является развитие иноязычной коммуникативной компетентности студентов, от уровня сформированности которой зависит успех их профессиональной деятельности в будущем. The structure of the problem-the communicative approach and presents an analysis of the results of its implementation in the process of foreign language teaching of future specialists in international relations. The purpose of a pilot implementation the above approach is the development of foreign language communicative competence of students, from the level of formation of which depends the success of their professional activities in the future. The results of training of future specialists on the basis of the problemcommunicative approach have shown a high level of development of foreign language communicative competence. The use of problem-communicative approach contributed to the positive dynamics in the change of mental states of the future specialists of the experimental group in comparison with the similar indicators of the students in the control group.